The Spiritual Tasks of Aging towards Death - DeVries, Dawn (Interpretation, 2021)
This article presents experiential reflections on the spiritual tasks for the last stage of human life. These tasks—experiencing escalating losses, accepting growing dependence on others, reframing the meaning of one’s life, and finding purpose even as one slowly lets go of life—are challenging, at least in part because they are counter-cultural for twenty-first century Americans. Exploring the spiritual tasks of aging towards death is necessary and important work for both aging elders and those who accompany them on the last stage of their life’s journey.